2013
DOI: 10.3109/21691401.2013.853178
|View full text |Cite
|
Sign up to set email alerts
|

Carrier free immobilization and characterization of trypsin

Abstract: Pancreatic trypsin was immobilized by cross-linked enzyme aggregates (CLEA) which is a carrier free immobilization method. Ammonium sulfate was chosen for enzyme precipitation which was followed by cross linking of formed aggregates via glutaraldehyde. Concentrations of precipitant and cross linker were respectively optimized as 60% ammonium sulfate and 1% glutaraldehyde. Optimum pH and temperature for CLEA was increased compared to free enzyme. Furthermore, pH, thermal and storage stability were improved. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In addition, immobilized trypsin showed higher activity compared to the free trypsin enzyme, both at pH 6.0 and at alkaline pH (pH 9.0). These results are in accordance with previous results described in literature, where improved pH stability of enzymes upon immobilization was reported for trypsin (Menfaatli and Zihnioglu, 2015;Sun et al, 2017), lipase (Mohamed et al, 2011 and catalase (Abdel-Mageed et al, 2012) were reported.…”
Section: Effect Of Ph On Trypsin Activitysupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, immobilized trypsin showed higher activity compared to the free trypsin enzyme, both at pH 6.0 and at alkaline pH (pH 9.0). These results are in accordance with previous results described in literature, where improved pH stability of enzymes upon immobilization was reported for trypsin (Menfaatli and Zihnioglu, 2015;Sun et al, 2017), lipase (Mohamed et al, 2011 and catalase (Abdel-Mageed et al, 2012) were reported.…”
Section: Effect Of Ph On Trypsin Activitysupporting
confidence: 93%
“…In this study, ammonium sulfate was chosen for precipitation of trypsin as a mild precipitant and preferred over other organic solvents due to its minimal effect on enzyme activity (Velasco-Lozano et al, 2015). Precipitation using ammonium sulfate was previously reported by several authors (López-Serrano et al, 2002;Yu et al, 2006;Menfaatli and Zihnioglu, 2015). The second stage of CLEA preparation is the cross-linking step of the precipitated enzyme aggregates.…”
Section: Preparation Of Trypsin Cleasmentioning
confidence: 99%
See 2 more Smart Citations